Drug Delivery via the Suprachoroidal Space for the Treatment of Retinal Diseases - Liron Naftali Ben Haim; Elad Moisseiev (MDPI AG, 2021)
The suprachoroidal space (SCS), a potential space between the sclera and choroid, is becoming an applicable method to deliver therapeutics to the back of the eye. In recent years, a vast amount of research in the field has been carried out, with new discoveries in different areas of interest, such as imaging, drug delivery methods, pharmacokinetics, pharmacotherapies in preclinical and clinical trials and advanced therapies. The SCS can be visualized via advanced techniques of optical coherence tomography (OCT) in eyes with different pathologies, and even in healthy eyes. Drugs can be delivered easily and safely via hollow microneedles fitted to the length of the approximate thickness of the sclera. SCS injections were found to reach greater baseline concentrations in the target layers compared to intravitreal (IVT) injection, while agent clearance was faster with highly aqueous soluble molecules. Clinical trials with SCS injection of triamcinolone acetonide (TA) were executed with promising findings for patients with noninfectious uveitis (NIU), NIU implicated with macular edema and diabetic macular edema (DME). Gene therapy is evolving rapidly with viral and non-viral vectors that were found to be safe and efficient in preclinical trials. Here, we review these novel different aspects and new developments in clinical treatment of the posterior segment of the eye.